Measurement of the reproductive efficiency of Arabian stallions intended for AI in Algeria - H, HOUSSOU; F, BOUZEBDA-AFRI; Z, BOUZEBDA; M, BENIDIR; K, BOUJAKJI A (The Indian Journal of Animal Sciences, 2021)
The aim of this study was to determine the reproductive efficiency of Arabian stallions presented at CNIAAG and selected for an artificial insemination (AI) program. Ten Arabian stallions between 8 and 15 years of age were subjected to an analysis of the reproductive parameters. Assessment of sexual behaviour, testicular measurements and appreciation of semen quality collected with the help of artificial vagina was done. There was a significant correlation between the sexual behaviour, the spermatic parameters and the testicular parameters, especially between the number of mounts with the motility and the daily sperm ejaculated (DSP) (r=0.99). The testicular volume total and mounts was highly correlated to the average volume of ejaculate (73.33 Â± 60.27 ml) and total Sperm concentration (billions) (r=0.99) which allowed us to produce 38 straws intended for the preservation. Based on the results, it is concluded that there is a positive correlation between (TSW) and motility, the various measurements of testis size were highly correlated with each other; and consequently to predict the fertility of the stallions from the testicular measurements.